Responsivity of Periaqueductal Gray Connectivity Is Related to Headache Frequency in Episodic Migraine - Solstrand Dahlberg, Linda; Linnman, Clas N.; Lee, Danielle; Burstein, Rami; Becerra, Lino; Borsook, David (Frontiers in Neurology, 2018)
Abstract Migraineurs show hypersensitivity to sensory stimuli at various stages throughout the migraine cycle. A number of putative processes have been implicated including a dysfunction in the descending pain modulatory system in which the periaqueductal gray (PAG) is considered to play a crucial role. Recurring migraine attacks could progressively perturb this system, lowering the threshold for future attacks, and contribute to disease chronification. Here, we investigated PAG connectivity with other brain regions during a noxious thermal stimulus to determine changes in migraineurs, and associations with migraine frequency. 21 episodic migraine patients, and 22 matched controls were included in the study. During functional MRI, a thermode was placed on the subjects’ temple delivering noxious and non-noxious heat stimuli. A psychophysiological interaction (PPI) analysis was carried out to examine pain-induced connectivity of the PAG with other brain regions. The PPI analysis showed increased PAG connectivity with the S1 face representation area and the supplementary motor area (SMA), an area involved with pain expectancy, in patients with higher frequency of migraine attacks. PAG connectivity with regions involved with the descending pain modulatory system (i.e. prefrontal cortex) was decreased in the migraineurs vs. healthy individuals. Our results suggest that high frequency migraineurs may have diminished resistance to cephalic pain and a less efficient inhibitory pain modulatory response to external stressor (i.e., noxious heat). The findings support the notion that in migraine there is less effective pain modulation (viz., decreased pain inhibition or increased pain facilitation), potentially contributing to increased occurrence of attacks/chronification of migraine.